Respiratory Viruses in a Primary Health Care Facility in Amsterdam, the Netherlands. Issue 4 (July 2018) - Bruning, Andrea H.L.; de Kruijf, Wilhelmina B.; van Weert, Henk C.P.M.; Vrakking, Anja; de Jong, Menno D.; Wolthers, Katja C.; Pajkrt, Dasja
Abstract : Background: Laboratory testing for respiratory tract infections (RTIs) is not routinely performed in primary care. Their etiology is usually unknown, and although RTIs are mainly of viral origin, the contribution of different respiratory viruses is uncertain. Our study aims to increase our insight into the epidemiology of respiratory viruses in primary care and to evaluate the accuracy of the general practitioner's (GP's) clinical diagnosis of influenza virus infection. Methods: We prospectively recruited patients who presented with RTI symptoms at a primary care facility in Amsterdam, the Netherlands, during the 2015–2016 winter season. Demographic and clinical characteristics of patients were summarized using a questionnaire. Nasopharyngeal swabs were collected and tested with a multiplex polymerase chain reaction assay detecting 14 respiratory viruses. Results: One or more respiratory viruses were present in 42.5% of the patients (n = 353). The most frequently detected viruses were rhinovirus (11.6%), human coronavirus (8.8%), and influenza A virus (7.6%). Sensitivity of GP's clinical diagnosis for influenza virus infection was 52.6% and specificity was 78.3%. Conclusions: Despite the use of a sensitive polymerase chain reaction, a respiratory virus could be detected in less than half of the patients visiting the GP with RTI symptoms. It is difficult to clinically distinguish influenza from other causes of RTIs. Correct etiological diagnosis of RTIs is needed because it contributes to differential diagnosis, might give direction to development of specific antiviral therapies and vaccines, reduce unnecessary prescription of antibiotics, and clarifies the clinical spectrum of the different respiratory viruses. Abstract : This prospective study describes the epidemiology of respiratory viruses and evaluates the accuracy of general practitioners' (GPs') clinical diagnosis of inf luenza virus infection in a primary care facility in the Netherlands during the 2015–2016 winter season. At least one virus was present in 42.5% of the patients with respiratory symptoms. Rhinovirus, coronavirus, and inf luenza A virus were most frequently detected. It was difficult for GPs to clinically distinguish inf luenza from the other respiratory viruses.